The impact of supervisory justice and perceived Supervisor support on organizational citizenship behavior and commitment to supervisor: the mediating role of trust - Ammara Akram; Muhammad Kamran; Muhammad Shahid Iqbal; Ume Habibah; Muhammad Atif Ishaq (Cogent Business & Management, 2018)
This study examines the mediating role of supervisory trust between the relationship of supervisory justice & perceived supervisor support and organizational citizenship behavior & commitment to supervisor. Drawing on social exchange theory and justice theory, we hypothesize that supervisory justice and perceived supervisor support will significantly affect trust in supervisor which in turn enhances subordinate organizational citizenship behavior and commitment to supervisor. Data was collected from 350 employees of telecommunication sector of Pakistan through a self-administered survey. Structural equation modeling (SEM) technique was applied via LISERL to test the hypothesized model. The results revealed that supervisory justice (interpersonal, and informational justice) and perceived supervisor support are positively and significantly related to organizational citizenship behavior and commitment to supervisor except for supervisory procedural justice. Moreover, trust in supervisor partially mediates the relationship between supervisory justice (interpersonal, and informational justice) & perceived supervisor support and organizational citizenship behavior & commitment to supervisor. However, the mediation of supervisory trust was not supported for supervisory procedural justice and organizational citizenship behavior & commitment to supervisor. Based on the results, theoretical, practical implications, and future research directions are discussed.
Keywords: 650